2016
DOI: 10.2135/cropsci2015.07.0441
|View full text |Cite
|
Sign up to set email alerts
|

Seed Yield of Norwegian and Swedish Tetraploid Red Clover (Trifolium pratense L.) Populations

Abstract: While tetraploid plants of red clover are taller, have thicker stems, and have broader leaves that altogether result in a higher forage yield compared to diploids, they generally have substantially lower seed yields than diploid plants. Tetraploid red clover can be induced chemically by colchicine or nitrous oxide (N2O) and sexually by union of unreduced gametes. The average seed yield of tetraploid red clover in Norway is 60% of the diploid yield, while in Sweden it is 75%. One objective of this paper was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 12 publications
2
28
0
Order By: Relevance
“…Seed yield per flower head was also identified as the component most strongly correlated (r = 0.96 and 0.98) with seed yield per area in two multisite dense-stand seed production experiments with twelve tetraploid cultivars and breeding populations (Amdahl et al, 2016). Similarly, in the current study, SYFH was also identified to be the most strongly correlated (r = 0.91 and 0.68 in experiments one and two, respectively) with the SYP.…”
Section: Single-plant Versus Dense Plant Canopysupporting
confidence: 73%
See 4 more Smart Citations
“…Seed yield per flower head was also identified as the component most strongly correlated (r = 0.96 and 0.98) with seed yield per area in two multisite dense-stand seed production experiments with twelve tetraploid cultivars and breeding populations (Amdahl et al, 2016). Similarly, in the current study, SYFH was also identified to be the most strongly correlated (r = 0.91 and 0.68 in experiments one and two, respectively) with the SYP.…”
Section: Single-plant Versus Dense Plant Canopysupporting
confidence: 73%
“…As evidenced in our dense plant canopy trials (Amdahl et al, 2016), differences in seed yield between tetraploid cultivars are likely to be more prominent under optimal weather conditions. In experiment two, SFH, SYFH and FERT showed a tendency of being higher in cultivars that gave the highest SYP; however, these differences were not significant.…”
Section: Comparison Of Seed-yield Components In Several Tetraploid Rementioning
confidence: 70%
See 3 more Smart Citations